PENGARUH CITRA DESTINASI TERHADAP KEPUTUSAN BERKUNJUNG DI OBJEK WISATA PANTAI CAROCOK PAINAN - Putra, Edri Sulsa; Yuliana, Yuliana; Suyuthie, Hijriyantomi (Journal of Home Economics and Tourism, 2017)
The purpose of research is to determine the effects of destination image toward decision to visit in Pantai Carocok Painan. The type of research is classified as associative causal. The population in this research is the visitors who come to visit Pantai Carocok Painan. The sampling technique in this research is the incidental sampling of 100 people. Data collection technique is done by spreading the questionnaire by using Likert scale that has been tested the validity and reliability. Further data is simple linear regression analysis and determinant coefficient analysis (R square), using SPSS Computer Program 16.00. The results showed that: (1) The image of the destination was in good category (59%). (2) The visiting decision is in good category (40%). (3) The result of simple linear regression test is obtained with R Square equal to 0,504 with sig level. 0,000 <0.05. This means that the destination image influences the visiting decision significantly by 50.4%, and the remaining 49.6% is influenced by other factors.Keywords: Destination Image, Decision to Visit